PERSPECTIVE OF INTERNATIONAL LAW ON MARITIME DISPUTE: CASE BETWEEN KENYA AND SOMALIA - Gunawan, Yordan; Salim, Andi Agus; Asirwadana, Ewaldo; Prasetyo, Satya Bayu (Unissula, 2021)
The research analysed the maritime dispute between Kenya and Somalia under the international law perspective. Both states have been experiencing maritime disputes over maritime boundaries of more than 100,000 sq km of seabed in the waters of the Indian Ocean. They began to clash after Somalia accusing Kenya of illegally granting exploration rights to resources in the waters to multinational companies, Total and Eni. As Kenya declared, the waters of the East African Coast are one of the hottest oil exploration prospects in the world, and the contested area has hydrocarbon reserves. The research method is normative legal research. Accordingly, the nature of the research was descriptive-qualitative with data collection techniques by conducting a literature study. The research shows that maritime boundary dispute has worsened diplomatic relations between Kenya and Somalia. Prior to bringing the case to the International Court of Justice (ICJ), the two states agreed to resolve the dispute through bilateral negotiations. However, the case was still unsettled. Therefore, Somalia decided to bring the case before the Court.